Study of the Effect of the Orchestra Pit on the Acoustics of the Kraków Opera Hall - KAMISIŃSKI, Tadeusz; BURKOT, Mirosław; RUBACHA, Jarosław; BRAWATA, Krzysztof (Archives of Acoustics, 2009)
The orchestra pit acoustics are mostly assessed by musicians and directors of musical performances using the sense of hearing, i.e. in a subjective manner. This paper proposes a method for an objective assessment using such parameters as Support (ST) and Sound Strength (G), which are obtained by measurements. ST defines the quality of how orchestral musicians hear one another in the orchestra pit, whereas G determines the impression of loudness at selected points of the auditorium. To determine the value of these parameters, acoustic measurements were performed in the orchestra pit and the auditorium of the Kraków Opera Hall. A numerical model was also developed, which was employed for multivariant computer simulations using the CATT-acoustic software. The purpose of the paper is to present a methodology for objective assessment of the orchestra pit acoustics.